A project management framework for enhanced productivity performance using building information modelling (Construction Economics and Building, 2017)
Although the Singapore government has mandated submissions of building plans in building information modelling (BIM) format since July 2013, this does not yet seem to lead to enhanced productivity performance. BIM collaboration between designers and downstream contractors appears to remain inadequate. While many studies have been conducted on using BIM for better project outcomes, studies that relate BIM with the identification of non-value adding activities in the project lifecycle and the reduction of the resulting wastes are at infancy stage. This paper aims to propose a project management framework for enhancing the productivity of building projects in Singapore, which forms Phase I of an ongoing research project. A two-pronged approach is presented. Firstly, non-value adding activities in the current project delivery process that uses BIM partially in Singapore are identified by comparing the typical current process with full BIM-based processes; such activities are cut down after process transformation in terms of people, process, and technology. Secondly, time savings derived from reducing the wastes caused by these activities are quantified. The proposed framework was validated by a case study of a local residential project. It was concluded that this framework provides a valuable tool for project teams to enhance productivity performance.